2012
DOI: 10.3389/fpsyg.2012.00087
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Representations of Internal and External Face Features are Used to Support Recognition

Abstract: Face recognition is impaired when changes are made to external face features (e.g., hairstyle), even when all internal features (i.e., eyes, nose, mouth) remain the same. Eye movement monitoring was used to determine the extent to which altered hairstyles affect processing of face features, thereby shedding light on how internal and external features are stored in memory. Participants studied a series of faces, followed by a recognition test in which novel, repeated, and manipulated (altered hairstyle) faces w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
2
13
1
Order By: Relevance
“…In particular, wearing a hijab obscures external features (such as hair and ears) which are naturally visible when viewing an unoccluded human face. Moreover, humans do not process faces as a collection of distinct facial features but rather as an integrated perceptual whole [ 30 , 31 ], and external features, like hair and ears, play an important role in this process ([ 7 , 32 ]; see also the external feature processing advantage [ 33 ]). For example, Toseeb and colleagues [ 7 , 32 ] found that wearing the hijab produces substantial differences in the way uncovered faces are recognized, and concluded that the external features of a face play an important role in face recognition and that facial processing changes when these features are not visible.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, wearing a hijab obscures external features (such as hair and ears) which are naturally visible when viewing an unoccluded human face. Moreover, humans do not process faces as a collection of distinct facial features but rather as an integrated perceptual whole [ 30 , 31 ], and external features, like hair and ears, play an important role in this process ([ 7 , 32 ]; see also the external feature processing advantage [ 33 ]). For example, Toseeb and colleagues [ 7 , 32 ] found that wearing the hijab produces substantial differences in the way uncovered faces are recognized, and concluded that the external features of a face play an important role in face recognition and that facial processing changes when these features are not visible.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that positive emotions lead to greater holistic processing of faces, whereas negative emotions are linked with feature-based processing ( Curby et al, 2012 ). Given that memory representation of face is holistic ( Chan and Ryan, 2012 ; Heptonstall et al, 2013 ), a test face with a happy expression should facilitate, whereas a test face with an angry expression should impair the retrieval process in an identity recognition task. Our results were consistent with this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, the present study revisits the issue of SF tuning for upright and inverted faces while taking into account two additional ecologically relevant parameters that may influence SF tuning: the presence of natural facial contour and face size. Given that external facial features such as natural facial contours do contain information useful for face identification (Ellis, Shepherd, & Davies, 1979;Chan & Ryan, 2012;Hills, Romano, Davies-Thompson, & Barton, 2014; but see Butler, Blais, Gosselin, Bub, & Fiset, 2010), it is possible that real-world differences between upright and inverted face SF processing were missed in previous studies using smaller face stimuli. Thus, we investigate in Experiment 1 the, to the best of our knowledge, unexplored issue of the role of natural facial contour in the SF tuning of upright and inverted faces.…”
Section: Introductionmentioning
confidence: 95%